Hidden gems reimagining the public realm along independence avenue to sustain the local economy in the Windhoek central business district - Persaud, Gwen (School of Architecture, Planning and Geomatics, 2025)
This urban design research project investigates the reimagining of the public realm along Independence Avenue to sustain the local economy in the context of the Windhoek Central Business District (CBD). The research seeks to explore how the public spaces can be transformed to support local businesses, foster Small, Medium, and Micro Enterprises (SMMEs) and stimulate overall economic development and growth. The research question drives this research to understand 'How can the public realm sustain the local economy?'. Through qualitative methodologies such as critical theory analysis of the relationship between economies and the public realm, rhythm analysis for field observations and semi-structured interviews, this research examines the current state of the public realm along Independence Avenue. The research analyses the role of urban design concepts like placemaking and human-centred design in shaping local economic activity. The findings highlight the untapped potential of “hidden gems” as clusters of local economic innovation that can be reinforced. The research highlights the significance of accessibility, connectivity, optionality and placemaking principles in creating a vibrant and thriving public realm that empowers both local businesses and the broader community. By contextualising this CBD regeneration to a postcolonial urban environment, this research contributes to an existing body of knowledge on urban regeneration and local economic development. It provides actionable recommendations for stakeholders and policymakers to enhance the public realm in a way that promotes sustainable economic growth in the Windhoek CBD. In doing so, it also presents valuable insights into how urban design can play a key role in fostering economic resilience and innovation in the context of Windhoek